Challenging hernias: a case series of atypical hernias and review of literature - Shanthi, P. S.; Kawarat, Vikas C.; Shankar, Adithi (International Surgery Journal, 2023)
Atypical hernias encompass the categories of flank, lumbar, spigelian, suprapubic and subxiphoid hernias among other rarer variants. These are considered to be tribulation in terms of their diagnosis and management, in that they are in proximity to the bone, which makes defect delineation, adequate mesh overlap, and fixation very challenging. Here, we would like to highlight a selection of our institutional experience with such hernias and their management. Within the institution, 6 cases of such rare hernias repaired within the last 6 months were chosen that posed a therapeutic challenge to the operating team. The cases described are- an interparietal port site incisional hernia, true lumbar hernia, flank region incisional hernia, a traumatic flank hernia, traumatic obstructed interparietal flank hernia, and a traumatic diaphragmatic hernia. All of the above cases were successfully managed by our team by a combination of abdominal wall reconstruction and mesh repair and have not reported any post-operative complications in the follow up period. Literature regarding rare hernia repairs is becoming more exhaustive by the day. However, the likelihood that we encounter such cases in practice is still less. Hence, it is essential to further the knowledge about management of such complex hernias and make an informed decision tailored to the patient’s requirements.